Taxonomy of the Alloraphes-Stenichnaphes-Parastenichnaphes complex: Stenichnodes complicates the picture (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2015)
Examination of the holotype of the type species of Stenichnodes Franz revealed that morphological structures of this Afrotropical genus are nearly identical with those of later described Oriental Parastenichnaphes Franz. Consequently, Parastenichnaphes is reduced to a subgenus of Stenichnodes, resulting in Stenichnodes (Parastenichnaphes) sumatrensis Franz, comb. n. and Stenichnodes (Parastenichnaphes) ceylonensis Franz, comb. n. The subgenus Parastenichnaphes differs from Stenichnodes s. str. in notosternal sutures of the prothorax complete (and not obliterated anteriorly), subtriangular (and not very narrow and carinate) prosternal process and absence of lateral metaventral carinae. Stenichnodes and its type species are redescribed.